2021
DOI: 10.1002/hbm.25729
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of the inverse base rate effect

Abstract: The inverse base rate effect (IBRE) is a nonrational behavioral phenomenon in predictive learning. Canonically, participants learn that the AB stimulus compound leads to one outcome and that AC leads to another outcome, with AB being presented three times as often as AC. When subsequently presented with BC, the outcome associated with AC is preferentially selected, in opposition to the underlying base rates of the outcomes. The current leading explanation is based on error-driven learning. A key component of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Wills et al (2014) previously reported preferentially common responding for cue compound DE, which was not observed in this experiment. This is the third time we have failed to replicate this particular aspect of our previous work under closely similar procedures; the other two were Experment 3 of Inkster (2019), and the experiment reported by Inkster, Milton, Edmunds, Benattayallah, and Wills (2021). Thus, contrary to Wills et al (2014), it seems likely that DE does not produce preferentially common responding in this procedure.…”
Section: The Exit Modelmentioning
confidence: 53%
“…Wills et al (2014) previously reported preferentially common responding for cue compound DE, which was not observed in this experiment. This is the third time we have failed to replicate this particular aspect of our previous work under closely similar procedures; the other two were Experment 3 of Inkster (2019), and the experiment reported by Inkster, Milton, Edmunds, Benattayallah, and Wills (2021). Thus, contrary to Wills et al (2014), it seems likely that DE does not produce preferentially common responding in this procedure.…”
Section: The Exit Modelmentioning
confidence: 53%
“…In the current experiment, each test stimulus was presented 12 times. Our previous work on the IBRE with EEG and MRI methodologies used similarly long test phases and the group-level results remained robust in these procedures (Inkster et al, 2021;Wills, Lavric, Hemmings, & Surrey, 2014), so we were confident that extending the test phase in this way would preserve the group-level results.…”
Section: Methodsmentioning
confidence: 73%
“…However, when participants are sequentially trained and tested on a combination of conflicting cues, the group-level result is that participants prefer the rare category (Kruschke, 1996). The IBRE has been observed in many experiments across a range of G-DISTANCE 20 scenarios (e.g., Shanks, 1992;Don & Livesey, 2017;Inkster, Milton, Edmunds, Benattayallah, & Wills, 2021;Inkster, Mitchell, Schlegelmilch, & Wills, 2022;Johansen, Fouquet, & Shanks, 2007, 2010Kalish, 2001;Sherman et al, 2009;Wills, Lavric, Croft, & Hodgson, 2007); for an excellent recent review, see Don, Worthy, and Livesey (2021).…”
Section: The Inverse Base-rate Effect (Ibre)mentioning
confidence: 99%
See 1 more Smart Citation
“…Johansen et al (2007) report a sample size of 16. If we use an effect size of d = 0.46 observed by Inkster, Milton, Edmunds, Benattayallah, and Wills (2022) and an α of 0.05 with a non-directional alternative hypothesis, the experiment has 24% power 1 . Given this information, this pilot experiment is underpowered.…”
Section: Related Workmentioning
confidence: 99%